2019
DOI: 10.1371/journal.pone.0212428
|View full text |Cite
|
Sign up to set email alerts
|

Children’s exposure to physical abuse from a child perspective: A population-based study in rural Bangladesh

Abstract: Background Although child physical abuse (CPA) is considered as a major global public health problem, it has not yet been recognized as such in Bangladesh. Very few studies have assessed the prevalence and victims’ characteristics of multiple forms of CPA. Objective This population-based study assessed the prevalence of CPA committed by adults in a rural area of Bangladesh and examined its association with demographic and socio-contextual factors. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
(55 reference statements)
2
12
1
1
Order By: Relevance
“…However, in some previous studies, higher rates of child PA (95%), PsyA (97%) and neglect (70%) were reported among normally developed children in Bangladesh [6,7]. So, the prevalence of different types of maltreatment reported in the present study is not exceptionally high than previous studies' findings in children without disabilities.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, in some previous studies, higher rates of child PA (95%), PsyA (97%) and neglect (70%) were reported among normally developed children in Bangladesh [6,7]. So, the prevalence of different types of maltreatment reported in the present study is not exceptionally high than previous studies' findings in children without disabilities.…”
Section: Discussioncontrasting
confidence: 79%
“…Studies from Bangladesh revealed almost all rural children aged 11-17 years, irrespective of their physical and mental conditions, faced at least one form of physical abuse (PA) or psychological abuse (PsyA) in the past year 6,7 . Although studies revealed that CM is highly prevalent in Bangladesh, there is no study regarding the prevalence of CM among children with ASD 6,8 . So, we aimed to determine the prevalence of CM in a selected group of Bangladeshi children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed methodology and the issues of ethical consideration have been outlined in a previous study 8 …”
Section: Methodsmentioning
confidence: 99%
“…Most physical and sexual violence against children and the elderly are hidden, especially in rural areas. A small amount of evidence shows that because of fear of the perpetrator, fear of not being believed, and not being noticed or asked, children usually do not disclose violent behavior incidences and do not seek violence-response services [46,47]. Additionally, some studies have highlighted the higher vulnerability of male victims of sexual abuse for reporting the incidence [48,49].…”
Section: Plos Onementioning
confidence: 99%